Rethinking representative democracy in Croatia - Butković, Hrvoje (Frontiers in Political Science, 2024)
The article analyses the development of representative democracy in Croatia from its independence to today. During the 1990s, Croatia changed its electoral system several times and had a bicameral parliament. With the constitutional changes implemented in 2001, the legislative power was organized on a unicameral principle. At the same time, the previous semi-presidential system was replaced by a parliamentary one. These changes represent only the basic framework within which representative democracy in Croatia developed over time. An important milestone in this development was the introduction of preferential voting at the national elections in 2015, which allowed the voters to vote for a particular list and a specific candidate on that list. According to some, this improved the problematic state of inner-party democracy, although, for others, the reform was not far-reaching enough. Given that representative democracy does not function in a vacuum, the article also considers the impact of direct democracy on the functioning of representative democracy in Croatia. Referring to the Croatian experience, it argues that this complementary form of democracy had a positive impact on the quality of representative democracy in the country. Nevertheless, in the face of representative democracy in Croatia, many open questions still need to be addressed. The most important one is how to increase the turnout in the elections, which is still comparatively low and arguably related to the low trust in politics.